Organizing for sustainability - Mohrman, Susan Albers; Shani, Abraham B. (Bingley, U.K. : Emerald, 2011)
A large literature has been generated about sustainability, and many organizations, governments, communities, and citizens have focused on it. Yet, given how quickly the limits of the current models of the global economy are being approached, we must accelerate the rate at which we learn to operate differently. In this first volume of the Emerald series Organizing for Sustainable Effectiveness, our goal is to learn from some of the pioneers articulating these challenges and organizing to address them. There is an urgent need to grow the knowledge bases to guide the transition. For this reason, each chapter in this volume is crafted to bring together the knowledge of practice and theory. The chapters are based on rich empirical data about particular cases in which organizations are, individually or collectively, working to build a more sustainable future. The authors of these chapters also bring theoretical knowledge to bear on these case examples. In so doing, they test the applicability of the formal knowledge base about management and organizations, while refining, modifying, and extending it to increase its usefulness in addressing the challenges of organizing for sustainable effectiveness. By combining knowledge from multiple stakeholders and multiple disciplines, it is the intention of the authors in this book to contribute to the broader learning discourse through which practical organizing solutions are designed and research-based guidance is provided.
ch. 1. Organizing for sustainable effectiveness : taking stock and moving forward / Susan Albers Mohrman, Abraham B. (Rami) Shani -- ch. 2. Unilever's drive for sustainability and CSR : changing the game / Philip Mirvis -- ch. 3. On the road to corporate responsibility : the institutionalization of sustainability at Gap, Inc. / Christopher G. Worley -- ch. 4. towards a sustainable healthcare system : transformation through participation / Svante Lifvergren, Peter Docherty, Abraham B. (Rami) Shani -- ch. 5. Emergent collaboration and leadership for sustainable effectiveness : the metropolitan housing authority / Ann E. Feyerherm, Sally Breyley Parker -- ch. 6. Managing sustainability : the port of Los Angeles among an ecology of organizations / Jan Green Rebstock, Hilary Bradbury-Huang -- ch. 7. Building multi-stakeholder sustainability networks : the Cuyahoga Valley Initiative / Christopher G. Worley, Sally Breyley Parker -- ch. 8. Organizing for sustainable effectiveness : reprise and way forward / Abraham B. (Rami) Shani, Susan Albers Mohrman.
Includes index.
Mode of access: World Wide Web.
Keywords: Sustainable development; Industrial management